Ethnomathematics: Exploration In Kebyok Anting- Anting Dance Floor Patterns For Learning The Concept Of Geometry - Rafi Rohayati; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi (IKIP Siliwangi, 2022)
Ethnomathematics is a realistic approach to learning mathematics that relates mathematical concepts to culture. By learning mathematics relevant to the student environment's culture, students will more easily understand mathematical concepts. This study aimed to examine theethnomathematical exploration of the Kebyok Anting-Anting dance floor pattern for learning the concept of geometry. This research is qualitative research using the ethnographic method. The instruments used are interviews, observation, and documentation. Data obtained through interviews and observations were analyzed using the analytical method described by Miles & Huberman, there are data reduction, data data display, and conclusion drawing/verification. The results showed that the ethnomathematical investigation in the Kebyok Anting-Anting dance floor patterns for learning the concept of geometry were horizontal lines, vertical lines, squares, rectangles, isosceles trapezoids, isosceles triangles, and parallelograms. It is hoped that various local cultures can be used to introduce other mathematical concepts.